Smart Card Berbantuan Wordwall Materi Ekosistem Melalui PBL Meningkatkan Adversity Quotient Kelas V SD - Oktriananda, Kana; Fatih , Mohamad; Wafa, Khoirul (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This research aims to develop a Wordwall-assisted Smart Card with a focus on ecosystem material, as well as increasing students' Adversity Quotient. In addition, this research also aims to test the effect of using Smart Cards assisted by Wordwall on Adversity Quotient abilities in grade V elementary school students. The approach used in this research is Research and Development (R&D), following the development steps proposed by Borg and Gall. The results of validation from media experts showed a score of 95%, while validation from material experts obtained a score of 94%. Both results are included in the "Very Valid" category. Based on student responses, the use of Smart Card media assisted by Wordwall showed a significant increase in the experimental class. This is evidenced by the results of the paired t-test whichmshows a significance value (2-tailed) of 0.00 which is smaller than 0.05. On the other hand, the control class also showed a significance result (2-tailed) of 0.003 which is also smaller than 0.05. In the hypothesis test, analysis using the Independent t-test resulted in a significance value (2-tailed) of 0.001 which is smaller than 0.05. Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.